Effects of heat pump scheduling on low‐voltage grids using a receding horizon control strategy - Michael Haendel; Gabriela Hug; Marian Klobasa (IET Smart Grid, 2023)
Abstract Heat pumps (HPs) are a promising option for decarbonizing the residential heating sector. Their use leads to an increased demand for electricity, which can burden the grid in uncontrolled operation, while controlled HPs can provide additional flexibility to the system. In this paper, the integration of HPs through a receding horizon approach into a power market model is presented to study the behavior of HPs considering electricity market prices and network constraints of a low‐voltage grid. In a case study with centralized and self‐consumption optimized control strategies, the effects of HPs are analyzed. Furthermore, the authors investigate how the aggregation of several households into energy communities affects the system. The results show that for the considered grid, the additional power demand of HPs is usually uncritical and a strictly cost‐minimizing operation is often possible from a grid perspective. Typically, critical grid situations occur only at times of high PV feed‐in with low HP flexibility. The formation of energy communities compared to individual households differs primarily in the allocation of cost savings to individual consumers. The difference in the impact of the two control strategies on the grid is negligible in this case.